ANALISA DAN PERANCANGAN LAYANAN JASA SETTING ATAU EDITTING DAN DIGITAL PRINTING BERBASIS WEB STUDI KASUS : CV. KARYA CIPTA MANDIRI - Senna Arliandi, - (2019)
This research was conducted to develop an information system in the form of a web-based application on CV. Karya Cipta Mandiri in analyzing and designing service requests for setting or editing and digital printing services, because all this time it only displays information about the company and all the processes are done manually, so customers often find it difficult to order. The purpose of this study is to help or facilitate digital printing CV.Karya Cipta Mandiri in developing requests for setting or editing and digital printing services to customers, so that the company is able to get new customers and utilize customer information that is useful for increasing transaction value and maintaining customer loyalty. This research was developed through a method of collecting data in the form of observation, interviews and literature. Data were analyzed using the PIECES framework (Performance Information Economic Control Efficiency Service). While the methodology used by the author in developing the system is the Waterfall method. While the analysis and design of the application is described using the UML (Unifed Modeling Language) method. This method was chosen because it can make a complete and precise design of the application implementation. It is expected that the relationship between the company and the customer can be established well, which in turn brings benefits to the company and so this system can help all parts in the ordering service